Classification of Exact Solutions for Generalized Form of K(m, n) Equation - Bulut, Hasan (Hindawi Ltd, 2013)
The classification of exact solutions, including solitons and elliptic solutions, to the generalized K(m, n) equation by the complete discrimination system for polynomial method has been obtained. From here, we find some interesting results for nonlinear partial differential equations with generalized evolution.
Keywords: Nonlinear Evolution